MOTIVASI KONSUMEN DALAM MELAKUKAN PEMBELANJAAN ONLINE DI KOTA BLITAR - DENOK WAHYUDI SETYO RAHAYU (Universitas Islam Balitar, 2021)
Online shopping has recently become a consumer choice. The motivation of consumers in making online purchases includes factors of experience, trust, convenience, price, and knowledge. The purpose of the study was to determine the factors that motivate consumers to make online purchases. The research method uses direct observation and questionnaires to consumers in Blitar City who make online purchases. The research population is online shopping consumers in Blitar City. The sampling technique uses accidental sampling, namely online shopping consumers who coincidentally meet with researchers. The variable used is consumer motivation. The results showed that consumer motivation in doing online shopping showed results in the form of a percentage that respondents tended to choose experience and trust (93.33%), convenience (90.00%), price (86.67%), and continued knowledge (83.33%).